2021
DOI: 10.1177/1359105320988325
|View full text |Cite
|
Sign up to set email alerts
|

She “didn’t see my weight; she saw me, a mom who needed help breastfeeding”: Perceptions of perinatal weight stigma and its relationship with breastfeeding experiences

Abstract: Weight stigmatization is related to emotional and psychological distress including low self-esteem, body image dissatisfaction, depression, and anxiety; all linked with suboptimal breastfeeding outcomes. This qualitative descriptive study explored postpartum individuals’ recalled experiences of weight stigma during interactions with perinatal healthcare professionals and its perceived influence on their breastfeeding experiences. Semi-structured phone interviews were conducted with (n= 18) participants. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Patients felt devalued through repeated negative interactions with healthcare providers where the use of derogatory language [29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]59,60 and pejorative non-verbal behaviours [29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Theme 1: Verbal and Non-verbal Communication Of Weight Stigmamentioning
confidence: 99%
See 2 more Smart Citations
“…Patients felt devalued through repeated negative interactions with healthcare providers where the use of derogatory language [29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]59,60 and pejorative non-verbal behaviours [29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Theme 1: Verbal and Non-verbal Communication Of Weight Stigmamentioning
confidence: 99%
“…The patient-provider relationship was the primary source of conflict across the literature. Experiencing depreciating comments, [29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]59,60 not being listened to, 29,31,32,36,[39][40][41]43,46,48,51,54,57 and being "talked down to" [29][30][31][32]34,35,39,41,45,…”
Section: Theme 1: Verbal and Non-verbal Communication Of Weight Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…*Correspondence: tnagpal@ualberta.ca depression, gestational diabetes, and reduced breastfeeding [10][11][12]. Furthermore, there is a correlation between frequency of weight stigmatizing experiences in pregnancy and maternal body mass index (BMI), suggesting pregnant individuals who have higher weights or obesity are at greater risk of weight stigma and potential associated complications [11].…”
Section: Open Accessmentioning
confidence: 99%
“…Studies with non-pregnant individuals have consistently shown a relationship between experiencing weight stigma and poor health outcomes and behaviours such as glucose intolerance, increased risk for depression and eating disorders, and avoiding physical activity settings [ 6 9 ]. Weight stigma has also been associated with poor prenatal outcomes such as postpartum depression, gestational diabetes, and reduced breastfeeding [ 10 12 ]. Furthermore, there is a correlation between frequency of weight stigmatizing experiences in pregnancy and maternal body mass index (BMI), suggesting pregnant individuals who have higher weights or obesity are at greater risk of weight stigma and potential associated complications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%